2012
DOI: 10.1103/physrevb.85.035430
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and polarization modulation of quantum dot emission in a one-dimensional liquid crystal photonic cavity

Abstract: We demonstrate spectral and polarization modulation of chemically synthesized core-shell CdSe/ZnS quantum dots (QDs) embedded in a one-dimensional photonic cavity formed by a cholesteric liquid crystal (CLC) matrix. A Cano-wedge cell varies the pitch of the CLC leading to the formation of Grandjean steps. This spatially tunes the photonic stop band, changing the resonance condition and continuously altering both the emission wavelength and polarization state of the QD ensemble. Using high resolution spatially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 36 publications
(34 reference statements)
2
43
0
Order By: Relevance
“…When the devices shown in Figure 3 were excited with the 532 nm continuous wave laser, we observed characteristic emission for QDs coupling with the cholesteric cavity for both types of particle (Figure 3e,f). The results are consistent with recent reported data from our group for ODA-QDs only [19,20]. In the ODA-QD device we observed that good cavity coupling as shown in Figure 3e as an example was very location dependent.…”
Section: Resultssupporting
confidence: 83%
“…When the devices shown in Figure 3 were excited with the 532 nm continuous wave laser, we observed characteristic emission for QDs coupling with the cholesteric cavity for both types of particle (Figure 3e,f). The results are consistent with recent reported data from our group for ODA-QDs only [19,20]. In the ODA-QD device we observed that good cavity coupling as shown in Figure 3e as an example was very location dependent.…”
Section: Resultssupporting
confidence: 83%
“…In cholesteric devices, embedded QDs can act as emitters coupled to a tunable fluid cavity, producing applications such as the quantum dot liquid crystal laser [32] and switchable cavities able to spatially modulate QD emission. [29,31] The efficiency of such devices will depend on our control of co-operative effects between adjacent particles. For example energy transfer processes such as FRET can reduce the efficiency of QD cavity coupling if the particles are closely packed in aggregates.…”
Section: Performance In Soft Photonic Devicesmentioning
confidence: 99%
“…This technique, applied previously by our group, [29][30][31] produces PL intensity maps of a 1 mm thick slice combined with emission spectra for each pixel recorded. PL microscopy provides a unique method for characterizing the distribution of fluorescent particles in liquid crystals, as energy-transfer processes, such as Forster resonance energy transfer (FRET), can be detected.…”
Section: Quantum-dot Organization In the Isotropic And Nematic Phasesmentioning
confidence: 99%
“…Another example of the assembly of QDs in nematic 5CB has been discussed by Ghosh and co-workers. [105][106][107] They have shown that nanodisks of GaSe at concentrations up to 10% assemble into ordered aggregates each composed of 15-60 GaSe nanodisks in the nematic phase of 5CB. 105,106 Emission spectra, optical textures and size distribution of GaSe clusters in the NLC mixture are shown in Fig.…”
Section: 98-101mentioning
confidence: 99%